PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP HARGA YANG BERIMPLIKASI PADA KEPUTUSAN PEMBELIAN AIR MINERAL DALAM KEMASAN MERK LE MINERALE (STUDI KASUS DI PT SUMBER ALFARIA TRIJAYA TBK, CIKOKOL TANGERANG) - Joonner Rambe; Cipta S. Panjaitan (Fakultas Ekonomi Universitas Borobudur, 2019)
This study aims to analyze more deeply the effect of product quality (X1) and promotion(X2) on prices (Y) which has implications for purchasing decisions (Z)The sampling technique uses semantic deferential, with a total sample of 80 people, the dataanalysis technique used in this study is the path analysis method and using an analysis tool that isSPSS 23.The test results show that the product quality variable has a positive and significant effectdirectly on price. Promotion has a positive and significant effect directly on prices. Productquality has a positive but not significant effect directly on purchasing decisions. promotion has apositive and significant effect directly on purchasing decisions. Prices have a positive andsignificant effect directly on purchasing decisions. Product quality has a positive and significanteffect indirectly on purchasing decisions through price. And promotions have a significantpositive and indirect effect on the decision of purchasing through prices.Keywords: Product Quality, promotion, price, and purchasing decisions